Prevalence and Contributing Factors of Childhood Trauma, Anxiety, and Depression Among Adolescents From Two-Child Families in China - Tong, Jie; Zhang, Tingting; Chen, Fazhan; Wang, Qiang; Zhao, Xudong; Hu, Manji (Frontiers in Psychiatry, 2022)
The Two-Child Policy has been implemented in China since 2016, which has attracted the attention of the world. The psychological status of adolescents may face huge challenges in the process of changing the family structure and relationship. To date, no mental health survey for adolescents of the two-child family has been conducted. We investigated the prevalence and risk factors of childhood trauma, anxiety, and depression of the two-child family in a statistically representative sample of Chinese senior high school students from Shanghai. 426 participants were randomly selected from 1059 students of four senior high schools in different districts of Shanghai. The childhood trauma questionnaire-short form (CTQ-SF), self-rating anxiety scale (SAS) and self-rating depression scale (SDS) was used as the screening tool. We found that the overall prevalence of childhood trauma, anxiety, and depression among senior high school students in the two-child family is 43.87%, 21.83% and 33.57% respectively, which are slightly higher than those in the one-child family. The two-child family is an important factor affecting childhood trauma, emotional neglect, and physical neglect (β=0.152, p<0.05; β=0.083, p<0.05; β=0.265, p<0.001). Ranking in the two-child family is a risk factor for childhood trauma (β=-0.135, p<0.05). Parental preference was a statistically significant correlation with physical abuse, physical neglect, anxiety, and depression (β=-1.581 to 0.088, p<0.05). Meanwhile, emotional abuse, physical abuse, emotional neglect, and physical neglect of two groups were positively correlated with anxiety and depression (r=0.195 to 0.478, p<0.05). There is a significant relationship between sexual abuse and anxiety symptoms of the one-child family group (r=0.161, p<0.05). The findings suggest that the prevalence of childhood trauma, anxiety and depression among adolescents from the two-child family in China is slightly higher than those from the one-child family, and was significantly correlated with factors such as two-child, family ranking and parental preference. These results highlight an urgent that needs to be addressed by adolescents` mental health service providers and policymakers.